Hepatitis B Virus Infection and Increased Risk of Gestational Diabetes Regardless of Liver Function Status: A Xiamen Area Population-Based Study - Zhao, Min; Yang, Shuyu; Su, Xiaojie; Hung, Tzu-Chieh; Liu, Yishan; Zheng, Wenjie (Frontiers in Physiology, 2022)
BACKGROUND & Aims: Hepatitis B virus (HBV) infection is a significant cause of liver function damage. However, previous studies on HBV are mainly aimed at ordinary people, and there is a lack of consensus on the relationship between HBV infection and gestational diabetes mellitus (GDM) and whether HBV-infected pregnant women should undergo antiviral treatment. In addition, systematic studies on the impact of HBV infection on GDM have rarely been studied directly. Therefore, the overall goal of this study was to pursue the association among HBV infection, liver function, and GDM using Xiamen area gestational big data. METHODS: Using the Xiamen Primary Health Information System-maternal and child health information system, the data on participants (138867 in total) expected confinement between 2008 and 2018 were included. Using univariate and multivariate logistic regressions, we constructed models to determine the role of HBV infection and liver function status in GDM. In addition, an analysis of Variance tests was performed to study whether the relationship between HBsAg and GDM differed in the normal liver function and the abnormal liver function subgroups. RESULTS: HBsAg positive status showed a substantial correlation with GDM onset in univariate and multivariate logistic regression (p<0.001). Subgroup analysis among HBsAg, liver function and GDM suggests that both HBsAg and liver function affect the onset of GDM and have the highest prevalence of both abnormalities. Further, ANOVA was used to investigate the association of HBsAg positive (p <0.001), abnormal liver function (p <0.001), and their interaction (p=0.302) on the onset of GDM. This result showed HBsAg is an independent factor of GDM pathogenesis regardless of liver function status. CONCLUSION: HBsAg and liver function were independent factors in GDM. Therefore, regarding these results, while clinicians consider the traditional risk factors of GDM, it is necessary to consider the HBV infection status. Conducting a dietary intervention for HBsAg positive pregnant women at the early stage of pregnancy is conducive to reducing the adverse effects.